A spin current detecting device working in the drift-diffusion and degenerate regimes - Mohammad Idrish Miah (Department of Physics, Sebelas Maret University, 2024)
A semiconductor-based device working in the spin drift-diffusion regime and for probing the injected or generated spin current was considered. The electric field effects on spin transport were analysed. A drift-diffusion equation for spin density was derived and contributions to the spin current were examined. By referring to the techniques of the spin current injection and generation, expressions for the spin current and spin-induced transverse Hall voltage arising from the injected or generated spin-polarized current were derived. The spin current and Hall voltage in dependences of the external electric field and temperature in the degenerate regime were studied. The device operated on the basis of with no external magnetic fields gives a voltage probe of the spin-induced Hall effect. Finally, a way of enhancing the spin current was explored.